2000
DOI: 10.1021/jp002032e
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Absorption Studies on the Photochromic Process of 2H-Benzopyrans in the Picosecond to Submillisecond Time Domain

Abstract: Picosecond to submillisecond photochromic reactions of 2,4-diphenyl-2H-benzopyran and 2,2,4-triphenyl-2H-benzopyran have been investigated by time-resolved absorption spectroscopy. The C−O bond cleavage of the benzopyrans (closed forms) occurs via the first excited singlet state within 2 ps to produce vibrationally excited open forms in the ground electronic state. In the subnanosecond to submillisecond time domain, several decay components with almost the same spectral profiles are observed. These components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 49 publications
3
34
0
Order By: Relevance
“…The yields of the major components with lifetimes of 48 s for Photochemistry of photochromic benzopyrans 149 2,4-Ph 2 BP and 12 s for 2,2,4-Ph 3 BP are linearly dependent on the nanosecond pump-laser power, while those of the minor components with longer lifetimes (>1 ms) are found to increase in the approximately second order of the nanosecond laser power 36 . This result indicates that the short-lived major components are produced through a one-photon process whereas the minor long-lived components are produced through a two-photon process within the duration of a pump-laser pulse (~ 20 ns).…”
Section: Photoisomerization Of the Open Forms Of Benzopyransmentioning
confidence: 91%
See 2 more Smart Citations
“…The yields of the major components with lifetimes of 48 s for Photochemistry of photochromic benzopyrans 149 2,4-Ph 2 BP and 12 s for 2,2,4-Ph 3 BP are linearly dependent on the nanosecond pump-laser power, while those of the minor components with longer lifetimes (>1 ms) are found to increase in the approximately second order of the nanosecond laser power 36 . This result indicates that the short-lived major components are produced through a one-photon process whereas the minor long-lived components are produced through a two-photon process within the duration of a pump-laser pulse (~ 20 ns).…”
Section: Photoisomerization Of the Open Forms Of Benzopyransmentioning
confidence: 91%
“…We have therefore performed time-resolved absorption studies on the photoexcitation dynamics of 2,4-diphenyl-(2,4-Ph 2 BP) and 2,2,4-triphenyl-2H-benzopyran (2,2,4-Ph 3 BP) from picoseconds to submilliseconds 36 . However, very little is known about the time developments of 2H-benzopyrans immediately after the photoexcitation, although knowledge on the dynamics in all the time range involved is essential for a detailed understanding of these photochemical reactions.…”
Section: Photochromic Behavior Of 2h-benzopyransmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds were investigated in different solvents ( polar vs. non-polar) 13 and for different excitation conditions, (S 1 vs. S N excitation) 19 using continuous-wave spectroscopy 12,13,15,22,23 or timeresolved techniques, e.g., transient absorption, TA. 14,[18][19][20]24,25 Based on the data from transient absorption measurements and the spectral dynamics observed after photoexcitation, at first a sequential model with fast excited state decay was suggested for the ring-opening reaction (Fig. 1a).…”
mentioning
confidence: 99%
“…The reversibility of the photochemical ring-opening was first reported by Bercovici et al [1] and since then there have been several experimental studies [2][3][4][5][6][7][8][9][10][11][12][13][14], including many on substituted spiropyrans and benzopyrans, which were considered as simplified models of spiropyrans. Recently, Buback et al [11] reported that the ring opening and closing processes of 6,8-dinitro-2 -3 -3 -trimethylspiro[2H-1-benzopyran-2-2 -indoline] (6,8-dinitro BIPS), as shown in Scheme 1, are reversible on a picosecond time scale, and this may lead to applications of spiropyrans as molecular switches.…”
Section: Introductionmentioning
confidence: 99%